HLA-Epitope Matching or Eplet Risk Stratification: The Devil Is in the Details - Tambur, Anat R. (Frontiers in Immunology, 2018)
.“Epitope matching” became a trending topic in organ transplantation. In fact, discussions on clinical implementation and utilization of this approach in organ allocation algorithms are currently on-going. More recently, the term “eplet mismatch load” was introduced in publications. While the terms are often used synonymously, they are NOT equivalent. This short overview is meant to emphasize the differences between the terms epitope matching and eplet mismatching (or mismatch load) as well as to provide perspective on different approaches for interpretation of immune compatibility between the donor of an organ transplant and the recipient. It highlights some of the less explored qualities of HLA-epitopes, and stresses the need to understand the differences between donor and recipient in terms of immunogenicity and ability to activate an immune response. While the field of “epitope matching” shows enormous promise, it is still in its infancy. What is sorely missing is understanding of EPITOPE COMPATIBILITY rather than matching. Further work is required before new approaches can be introduced into routine clinical practice and organ allocation schemes.